Against the Confrontation of Philosophy, Science and Religion - Nasikhin, Nasikhin (Online Journal of Research in Islamic Studies, 2023)
This article aims to carry out the execution of the confrontation between the understanding of philosophy, religion and science. By using library research, this study shows that the confrontation between philosophy, science and religion has a distinction that can be contested. First, philosophy is considered something that is very free because it thinks without limits. Contrary to religion which is based on revelation/inspiration from a substance that is considered God. While science is a device method to seek the truth. Everything that comes from God, in a religious perspective is a truth that cannot be rejected. Second, between philosophy and science, both do not have a central figure, unlike religion which centralizes God. Third, continuity between philosophy and science is generally used as a tool to sharpen understanding of religion, so that the truth about religion becomes stronger. This finding proves that the confrontation which states that philosophy, science, and religion are opposites can be rejected because science as a child of philosophy is a tool used by religious thinkers in understanding the meaning of revelation. This article recommends that future studies can strengthen the argument that philosophy, science, and religion should go hand in hand in discovering the essence of truth and wisdom.